2020
DOI: 10.5553/plc/258999292020002002005
|View full text |Cite
|
Sign up to set email alerts
|

Between Party Democracy and Citizen Democracy

Abstract: As a response to the perceived legitimacy crisis that threatens modern democracies, local government has increasingly become a laboratory for democratic renewal and citizen participation. This article studies whether and why local party chapters support democratic innovations fostering more citizen participation. More specifically, we analyse the relative weight of ideas, interests and institutions in explaining their support for citizen-centred democracy. Based on the Belgian Local Chairs Survey in 2018 (albe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Thirdly, we were limited by the formulation of the questions in the survey, which did not allow us to distinguish between binding and advisory innovations. Previous research (e.g., Caluwaerts et al, 2020;Jacquet et al, 2020) found that the binding nature of the innovation matters greatly, with support for binding referendums or mini-publics being lower than for advisory ones. However, the formulation of the items in the questionnaire remains vague on this issue, in the sense that it is not clear whether the referendums or mini-publics needed to be binding or advisory.…”
Section: Discussionmentioning
confidence: 94%
“…Thirdly, we were limited by the formulation of the questions in the survey, which did not allow us to distinguish between binding and advisory innovations. Previous research (e.g., Caluwaerts et al, 2020;Jacquet et al, 2020) found that the binding nature of the innovation matters greatly, with support for binding referendums or mini-publics being lower than for advisory ones. However, the formulation of the items in the questionnaire remains vague on this issue, in the sense that it is not clear whether the referendums or mini-publics needed to be binding or advisory.…”
Section: Discussionmentioning
confidence: 94%